Quantum computing with trapped particles in microscopic potentials - Calarco, T; Briegel, H; Jaksch, D; Cirac, J; Zoller, P (2000)
We review recent proposals for performing entanglement manipulation via controlled interactions between trapped atoms. State-dependent, time-varying microscopic potentials allow one to obtain with high fidelity a conditional phase shift realizing a universal quantum gate. We discuss possible physical implementations with existing experimental techniques, for example optical lattices and magnetic micro-traps.